Relationship between Critical Gap and Certain Geometrical Parameters in Roundabouts - Haitham, Al Hasanat; Schuchmann, Gábor (Periodica Polytechnica Civil Engineering, 2022)
Gap-acceptance method is one of the classical methods used to analyze capacity of roundabouts. Critical gap has a privileged role in this approach. Different driver behavior and local rules of traffic has a key role in implementing it in the local standard for capacity calculation in each country. Therefore, a reliable method for estimation of critical gap at a certain location can be of great importance. This paper presents the first steps of an experimental investigation and analysis on whether it is possible to find correlation between video-based gap acceptance data and certain design parameters of roundabouts in Hungary. Ten single lane roundabouts of different size were recorded for hours in different locations in and around Budapest to assess gap acceptance data and relate it to certain design parameters like diameter, distance of neighboring entries, entry width, width of splitter island, number of entries over time, and entry angle – or any combination of those. Using only a linear approach, strong positive correlation was found between measured critical gap and distance between legs. There is correlation (not so strong however) between critical gap and (approach) entry width as well as splitter island width, and enough data were examined to say that there is no correlation between central island diameter and critical gap.